Classical gonadoblastoma: its relationship to the 'dissecting' variant and undifferentiated gonadal tissue. Issue 4 (9th November 2017) - Roth, Lawrence M; Cheng, Liang
Abstract : Classical gonadoblastoma occurs almost entirely in the dysgenetic gonads of an individual who has a disorder of sex development. Approximately 40% of such neoplasms are bilateral. Almost all gonadoblastomas occur in patients who have a Y chromosome or part thereof; testis‐specific protein Y‐encoded 1 ( TSPY1 ) is the putative gene. If a gonad in a patient who has a disorder of sex development contains germ cells with delayed maturation, and also harbours the TSPY1 gene, the cells can undergo transformation to classical gonadoblastoma. The latter consists of rounded islands composed of germ cells, sex cord elements and hyaline basement membrane material surrounded by a variably cellular gonadal stroma that sometimes contains steroid cells. Classical gonadoblastoma can be interpreted as a non‐invasive neoplasm that is the precursor of germinoma and, indirectly, other more aggressive germ cell neoplasms. Undifferentiated gonadal tissue is the precursor of classical gonadoblastoma and contains germ cells with delayed maturation that express octamer‐binding transcription factor 4 (OCT4); however, other germ cells show normal maturation and express TSPY1. If all germ cells in a patient with undifferentiated gonadal tissue involute, the result is a secondary streak. Undifferentiated gonadal tissue is a non‐neoplastic condition that should be distinguished clearly from 'dissecting gonadoblastoma', a neoplasm derived from classical gonadoblastoma that is the precursor of some germinomas. 'Dissecting gonadoblastoma' is a variant of classical gonadoblastoma that has unusual growth patterns and contains both sex cord and germ cell elements. Clonal expansion of germ cells is a characteristic of the late stage of 'dissecting gonadoblastoma'.